Hubungan Antara Pengelolaan Kelas Dengan Prestasi Belajar Siswa SMP Negeri 2 Ende - Maimunah H. Daud; Indah Ukhrawi (Ekspektasi: Jurnal Pendidikan Ekonomi, 2018)
This study aims to find out whether or not there are connections between classroom management with the achievement studied physics grade VIII semester 4 SMP Negeri 2 Ende. Correlation between classroom management and student learning achievements with the value amounting to 0.692 rxy. The results showed that there were significant relationships between classroom management with the achievement studied physics grade VIII semester 4 SMP Negeri 2 Ende. This is demonstrated by the acquisition of r_hitung value = 0,692 > r_tabel = 0,239 determination coefficient with the contribution amounted to 47.8%.